Porous multi-element doped sludge carbon-based low-temperature denitration catalyst and preparation method thereof

Through the preparation method of porous multi-doped sewage peat-based low-temperature denitrification catalyst, the problem of poor performance of existing catalysts in medium and low-temperature flue gas environments is solved, efficient, economical and environmentally friendly low-temperature denitrification effect is achieved, and waste resource utilization is promoted.

CN119701976AInactive Publication Date: 2025-03-28GUANGDONG UNIV OF TECH +1

Patent Information

Application Number
CN202411766808.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing catalysts have poor catalytic activity in medium and low temperature flue gas environments, poor anti-sulfur poisoning performance, and poor water vapor tolerance, resulting in life attenuation and high replacement cost.

Method used

The porous multi-doped sludge-based low-temperature denitrification catalyst is used to pretreat the sewage peat precursor, and the ternary molten salt assists one-step carbonization activation, ultrasonic impregnation and microwave roasting are prepared to form porous peat particles loading the active components.

Benefits of technology

It significantly improves the catalytic activity and sulfur resistance of water resistance of the catalyst, extends the service life of the catalyst, reduces replacement costs, and realizes waste resource utilization, reduces the generation of harmful organic waste and carbon dioxide emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701976A_ABST
    Figure CN119701976A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses a porous multi-element doped sludge carbon-based low-temperature denitration catalyst and a preparation method thereof, relates to the technical field of air pollution control, and aims to solve the technical problem that the existing catalyst is generally poor in performance in a medium-low temperature flue gas environment. The preparation method comprises the following steps: obtaining target sludge; the method comprises the following steps: pretreating target sludge to obtain a sludge carbon precursor; performing ternary molten salt assisted one-step carbonization activation treatment on the sludge carbon precursor to obtain porous sludge carbon particles; mixing and dissolving the porous sludge carbon particles with a manganese precursor, a cobalt precursor and a rare earth metal Ce precursor in deionized water, adding a coupling agent, uniformly stirring and mixing, carrying out ultrasonic immersion treatment, and carrying out vacuum drying to obtain active component-loaded sludge carbon; the coupling agent is a silane coupling agent or a phthalate coupling agent; and carrying out microwave roasting treatment on the sludge carbon in an inert atmosphere to obtain the porous multi-element doped sludge carbon-based low-temperature denitration catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of air pollution control technology, and specifically relates to a porous multi-element doped sludge carbon-based low-temperature denitrification catalyst and a preparation method thereof. Background Art

[0002] Nitrogen oxides (NO x ) has caused a series of environmental problems such as photochemical smog, haze and acid rain, which have seriously harmed human health and the ecological environment. In recent years, a number of strict laws and regulations have restricted NO x Emissions, such as NO from key industries such as coal-fired power, steel, cement, and coking x All must meet ultra-low emission standards.

[0003] The mainstream process for industrial flue gas denitrification is currently the selective catalytic reduction (SCR) technology, the core of which is the catalyst. Commercial V2O5-WO3 / TiO2 catalysts are widely used in power plants for NO removal due to their high denitrification activity within the temperature window of 300-400°C. x control. Unlike coal-fired power plants, the flue gas temperature in non-electric industries such as steel, coking, industrial boilers, cement, glass, and waste incineration is relatively low. The denitrification unit is placed after the dust collector and desulfurization tower to avoid sulfur poisoning and catalyst blockage. However, after the flue gas is treated with desulfurization and dust removal, the temperature drops below 300°C, and the V2O5-WO3 / TiO2 catalyst has poor catalytic activity under medium and low temperature conditions. If additional heating is required, this will result in higher energy loss and economic costs, and increase carbon emissions. The catalyst also has problems such as complex preparation process, high cost, biological toxicity, and difficulty in handling after deactivation. Therefore, the development of medium and low temperature SCR denitrification catalysts for dust removal and desulfurization in non-electric industries is a good choice. x It is necessary and economical to remove the dust, reduce the wear of the catalyst and avoid the reheating of the flue gas. However, in the medium and low temperature flue gas environment, the existing catalysts generally have low catalytic activity, poor resistance to sulfur poisoning, poor water vapor tolerance, severe blockage and poisoning, and easy alkali metal poisoning, which leads to life decay and high catalyst replacement cost.

[0004] Therefore, it is urgent to develop a denitrification catalyst that is adaptable to low-temperature conditions, resistant to multiple poisonings, and efficient and economical. Summary of the invention

[0005] The main purpose of the present application is to provide a porous multi-element doped sludge carbon-based low-temperature denitrification catalyst and a preparation method thereof, aiming to solve the technical problem that existing catalysts generally have poor performance in medium and low temperature flue gas environments.

[0006] To achieve the above objectives, the technical solutions adopted in the embodiments of the present application are as follows:

[0007] In a first aspect, the present invention provides a method for preparing a porous multi-element doped sludge carbon-based low-temperature denitration catalyst, comprising the following steps:

[0008] Obtaining target sludge; pre-treating the target sludge to obtain a sludge carbon precursor;

[0009] The sludge carbon precursor is subjected to a one-step carbonization activation treatment assisted by a ternary molten salt to obtain porous sludge carbon particles;

[0010] The porous sludge carbon particles are mixed with a manganese precursor, a cobalt precursor and a rare earth metal Ce precursor, dissolved in deionized water, and a coupling agent is added. After stirring and mixing evenly, ultrasonic impregnation treatment is performed, and after vacuum drying, sludge carbon loaded with active components is obtained; the coupling agent is a silane coupling agent or a phthalate coupling agent;

[0011] The sludge carbon is subjected to microwave roasting treatment under an inert atmosphere to obtain a porous multi-element doped sludge carbon-based low-temperature denitration catalyst.

[0012] As some optional embodiments of the present application, the target sludge is non-hazardous waste sludge;

[0013] The step of pre-treating the target sludge to obtain a sludge carbon precursor comprises:

[0014] The target sludge is placed in a forced air drying oven at 80-110° C. and dried for 24 hours to a constant weight, and then the dried sludge is crushed by mechanical crushing, and the crushed sludge is sieved with a 40-mesh sieve to obtain a sieved sludge carbon precursor.

[0015] As some optional implementation modes of the present application, the mechanical crushing is ball mill crushing, and the rotation speed of the ball mill crushing is 200r / min to 400r / min, and the time is 3min to 10min.

[0016] As some optional embodiments of the present application, the step of subjecting the sludge carbon precursor to a one-step carbonization activation treatment assisted by a ternary molten salt, and then successively subjecting the sludge carbon precursor to extraction washing and vacuum drying to obtain porous sludge carbon particles comprises:

[0017] The sludge carbon precursor is mixed with ternary molten salt and heavy metal complexing agent, and then placed in a quartz boat;

[0018] The quartz boat is placed in a tubular furnace from which the air has been exhausted, and the temperature is raised to 600°C to 900°C for carbonization and activation treatment. After the carbonization and activation treatment is completed, the temperature is lowered to room temperature, and the boat is washed with dilute hydrochloric acid and deionized water to obtain porous sludge carbon particles.

[0019] As some optional embodiments of the present application, the mixing ratio of the sludge carbon precursor, the ternary molten salt and the heavy metal complexing agent is 1:1-10:0.01-0.1;

[0020] The ternary molten salt comprises lithium salt, potassium salt and sodium salt in a mass ratio of 1:1:1;

[0021] The heavy metal complexing agent includes one or more combinations of citric acid, oxalic acid, ethylenediamine, diethylenetriamine, triethylenetetramine, sodium nitrilotriacetate, sodium ethylenediaminetetramethylenephosphate, ethylenediaminetetraacetic acid, tetrasodium diaminetetraacetic acid and diethylenetriaminepentacarboxylate.

[0022] As some optional embodiments of the present application, the step of placing the quartz boat in a tube furnace from which air has been exhausted, heating it to 600° C. to 900° C. and then performing carbonization activation treatment; after the carbonization activation treatment is completed, cooling it to room temperature, washing it with dilute hydrochloric acid and deionized water, and obtaining porous sludge carbon particles comprises:

[0023] The quartz boat is placed in a tube furnace from which air has been exhausted, and the temperature is raised to 600°C to 900°C at a rate of 5 to 20°C / min, and then carbonized and activated;

[0024] After being kept at a constant temperature for 2 hours, the activated sludge was cooled to room temperature under an inert atmosphere, and then filtered and washed 5 to 10 times with dilute hydrochloric acid and deionized water to remove the molten salt crystallized on the surface and inside of the peat, thereby obtaining a porous structure.

[0025] The porous structure is vacuum dried to obtain porous sludge carbon particles.

[0026] As some optional embodiments of the present application, the inert atmosphere is nitrogen, helium or argon, and the flow rate of the inert atmosphere is 100 to 500 ml / min;

[0027] The concentration of the dilute hydrochloric acid is 1 mol / L to 3 mol / L;

[0028] The vacuum drying pressure is -0.06MPa to -0.08MPa, the vacuum drying temperature is 80°C to 110°C, and the vacuum drying time is 12h to 24h.

[0029] As some optional embodiments of the present application, the porous sludge carbon particles are mixed with a manganese precursor, a cobalt precursor and a rare earth metal Ce precursor and dissolved in deionized water, and a coupling agent is added, stirred and mixed evenly, and then ultrasonically impregnated, and vacuum dried to obtain the sludge carbon loaded with active components, comprising:

[0030] The precursor is a nitrate, sulfate, acetate or chloride of the corresponding metal; the silane coupling agent is one or more combinations of N-aminoethyl-y-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, y-methacryloxypropyltrimethoxysilane, y-mercaptopropyltrimethoxysilane and y-ureidopropyltriethoxysilane; the amount of the silane coupling agent added is 1% to 10% of the mass of the porous sludge carbon particles;

[0031] The mass fraction of the active components loaded in the porous sludge carbon is 5wt.%-25wt.%; wherein the molar ratio of manganese, cobalt and rare metal Ce is 1-5:1:0.05-0.3;

[0032] The ultrasonic frequency of the ultrasonic immersion treatment is 10KHz to 80KHz, and the ultrasonic immersion time is 2h to 5h.

[0033] As some optional embodiments of the present application, the step of subjecting the sludge carbon to microwave roasting in an inert atmosphere to obtain a porous multi-element doped sludge carbon-based low-temperature denitrification catalyst comprises:

[0034] The power of the microwave roasting treatment is 1000W to 3000W, the microwave roasting temperature is 600°C to 800°C, and the microwave roasting time is 1h to 3h;

[0035] The inert atmosphere flow rate is 20 ml / min to 50 ml / min.

[0036] In the first aspect, the implementation case of the present application also provides: a porous multi-element doped sludge carbon-based low-temperature denitrification catalyst prepared by the above method.

[0037] Compared with the prior art, the beneficial effects of this application are:

[0038] The raw material sludge of this application is a by-product of sewage treatment. It is pyrolyzed into porous sludge charcoal with high specific surface area and high mechanical strength using multi-component molten salt. Sludge charcoal has a high carbon content and can directly participate in heterogeneous denitrification reactions, and its porous structure makes it an ideal carrier for loading active components. This method of converting sludge into a solid reductant and denitrification catalyst carrier not only maximizes the resource utilization of waste, but also reduces the generation of harmful organic waste and the emission of carbon dioxide. It deeply reflects the concept of "waste treatment with waste" and provides new ideas for the disposal of solid waste sludge.

[0039] The present application comprehensively utilizes the low-temperature denitrification activity of Mn, the oxidation vacancies provided by the Ce element, and the acidic sites provided by the Co element, giving full play to the synergistic effect between the active components, enriching the acidic sites on the surface of the sludge carbon, effectively broadening the temperature window of the catalyst catalytic reaction, and greatly enhancing the catalyst's anti-sulfur and water resistance.

[0040] The preparation process described in the present application is simple, the composite molten salt can be recycled and reused, the sludge treatment cost can be obtained, the catalyst preparation cost is reduced, and a highly efficient, economical, water-resistant and sulfur-resistant porous multi-doped sludge carbon-based low-temperature denitrification catalyst is prepared. The catalyst is suitable for large-scale industrial production and can be widely used in industries with complex flue gases such as steel, coking, industrial boilers, cement, glass, and waste incineration. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a schematic diagram of the preparation method involved in the embodiment of the present application;

[0042] Figure 2 This is a graph showing the chemical composition analysis results of the sludge ash involved in the embodiments of the present application. DETAILED DESCRIPTION

[0043] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0044] Based on the problems existing in the prior art, the present application proposes a porous multi-element doped sludge carbon-based low-temperature denitrification catalyst and a preparation method thereof. The present application uses sludge as raw material, and uses lithium salt, sodium salt and potassium salt ternary molten salt to assist its one-step carbonization activation, and then washes the recrystallized molten salt with dilute hydrochloric acid and deionized water to obtain a porous sludge carbon that serves as both a carrier and a solid reducing agent. Then, the multi-element doped sludge carbon-based catalyst is synthesized by ultrasonic impregnation and microwave roasting. The interface bonding force and dispersion between the carrier and the active component are regulated by complexing agents and coupling agents, and the synergistic effect between the various active components is fully exerted, further improving the catalytic activity and sulfur and water resistance of the catalyst. The process is simple, the cost is low, and waste is treated with waste. It can be applied to SCR denitrification units in industries such as steel, coking, industrial boilers, cement, glass, and waste incineration.

[0045] Specifically, the above-mentioned purpose of the present application is achieved through the following technical solutions:

[0046] A porous multi-element doped sludge carbon-based low-temperature denitrification catalyst is mainly prepared by raw material pretreatment, ternary molten salt assisted one-step carbonization activation, ultrasonic impregnation, microwave roasting and other steps. The detailed preparation steps are as follows:

[0047] S1. Pretreatment of sludge: In the sewage treatment plant, the moisture content of the sludge after dehydration by the plate filter press is about 60%, and it is placed in a blast drying oven at 80-110℃ for 24 hours to a constant weight. Then the dried sludge is crushed by mechanical crushing, and the crushed sludge is screened with a 40-mesh screen to obtain the screened sludge carbon precursor.

[0048] Preferably, the mechanical crushing method in step S1 is usually ball milling, with a ball milling speed of 200-400 r / min and a time of 3-10 min.

[0049] Preferably, the sludge in step S1 is non-hazardous waste sludge, including but not limited to one or more of municipal sludge, industrial sludge, and oily sludge, and the main components of the sludge ash are SiO2, Al2O3, Fe2O3 and MgO.

[0050] S2. Ternary molten salt assisted one-step carbonization activation: The sludge carbon precursor obtained in step S1 is uniformly mixed with ternary molten salt and heavy metal complexing agent in a certain proportion by mechanical stirring, and then placed in a quartz boat and the quartz boat is placed in a tube furnace. Before heating the tube furnace, the horizontal tube furnace is purged with inert gas for 10 to 30 minutes to remove the air in the tube to ensure an inert atmosphere. The horizontal tube furnace is heated to a specified pyrolysis temperature at a certain heating rate, and the pyrolysis temperature is kept constant for 2 hours for sufficient carbonization and activation. After cooling to room temperature under an inert atmosphere, the carbonized and activated sludge carbon is washed 5 to 10 times with dilute hydrochloric acid and deionized water to remove the molten salt crystallized on the surface and inside of the peat to form a porous structure. Then, a porous sludge carbon with high mechanical strength is obtained by vacuum drying. The filtrate obtained by multiple filtration and washing is further digested to recover and reuse the molten salt to avoid waste of resources and environmental pollution.

[0051] Preferably, the inert gas described in step S2 is nitrogen, helium or argon; the inert gas flow rate is 100-500 ml / min, and the flow rate is determined according to the inner diameter length of the quartz tube of the horizontal tube furnace. When using a Φ60 / 53×1000mm quartz tube, the flow rate is usually set to 200 ml / min.

[0052] Preferably, the heating rate in step S2 is 5-20°C / min, and the pyrolysis temperature is 600-900°C.

[0053] Preferably, the heavy metal complexing agent described in step S2 includes one or more combinations of citric acid, oxalic acid, ethylenediamine, diethylenetriamine, triethylenetetramine, sodium nitrilotriacetate, sodium ethylenediaminetetramethylene phosphate, ethylenediaminetetraacetic acid, tetrasodium diaminetetraacetic acid and diethylenetriamine pentacarboxylate, and the amount of complexing agent added is 1-10% of the mass of the sludge carbon precursor. Taking sodium ethylenediaminetetramethylene phosphate as an example, its working principle is: through its phosphate group and metal ions to form a stable complex, the volatilization or migration of heavy metals during high-temperature roasting is reduced, and the heavy metal ions can be fixed on the carrier through complexation, and their valence state is adjusted, so that the heavy metal is easier to participate in the subsequent catalytic reaction and the activity of the catalyst is improved.

[0054] Preferably, the ternary molten salt described in step S2 refers to lithium salt, potassium salt and sodium salt with a mass ratio of about 1:1:1, including potassium carbonate (K2CO3), sodium carbonate (Na2CO3), lithium carbonate (Li2CO3), potassium chloride (KCl), sodium chloride (NaCl), lithium chloride (LiCl), potassium sulfate (K2SO4), sodium sulfate (Na2SO4), lithium sulfate (Li2SO4). More preferably, the ternary carbonate molten salt is composed of potassium carbonate, sodium carbonate and lithium carbonate.

[0055] Preferably, the mass ratio of the sludge carbon precursor to the ternary molten salt in step S2 is 1:(1-10).

[0056] The principle of ternary molten salt assisted one-step carbonization activation is that molten salt assisted pyrolysis can enhance heat transfer, impart catalytic effect and provide liquid phase reaction environment in the process of sludge thermochemical conversion. It has high catalytic efficiency in the medium and low temperature range, which helps to increase the carbon content and calorific value of biochar and reduce the content of volatiles. As the pyrolysis temperature gradually increases to the eutectic point, the molten salt is transformed from a solid state to a molten state, and the sludge particles are evenly distributed in it. The ions in the molten salt can better catalyze the pyrolysis and polymerization reactions of the sludge and promote the formation of a porous structure. In addition, under high temperature conditions, sludge charcoal reacts with CO2, water vapor released by itself, and CO2 produced by carbonate pyrolysis to produce carbon monoxide and hydrogen (such as reactions R1 to R3). On the other hand, it may also react with molten salt to produce carbon dioxide (such as reactions R4 to R7), further enhancing the pore structure through physical and chemical joint activation. During the cooling process, the salt will recrystallize and embed in the sludge carbon. At this time, the molten salt particles act as templates. Through the subsequent acid washing and water washing, the molten salt particles are removed to form more mesoporous or microporous structures inside the sludge carbon, thereby enhancing its adsorption capacity. Throughout the process, by controlling the temperature, time, type and concentration of molten salt during carbonization and activation, the structure, surface area, morphology and performance of the porous sludge carbon are regulated to obtain a rich pore structure, surface functional groups and active adsorption sites of the sludge carbon, thereby improving the NO adsorption capacity and NO reduction effect.

[0057]

[0058] Here, M represents Li, Na or K.

[0059] Preferably, the concentration of the dilute hydrochloric acid solution in step S2 is 1 mol / L to 3 mol / L. The role of the dilute hydrochloric acid is to dissolve the alkali metal oxides such as CaO, MgO, etc. in the sludge carbon, and retain the active components of the sludge carbon itself that are beneficial to denitrification, such as Fe2O3, MnO, etc.

[0060] Preferably, the vacuum drying parameters described in step S2 are: vacuum pressure -0.06MPa to -0.08MPa, temperature 80°C to 110°C, and time 12h to 24h.

[0061] S3. Ultrasonic impregnation of metal salt solution: Weigh a certain amount of manganese, cobalt and rare earth metal Ce precursors and the porous sludge carbon obtained in step S2 and dissolve them in a beaker filled with deionized water, then add a certain amount of silane coupling agent or phthalate coupling agent, stir the mixed solution with a magnetic stirrer for 0.5 hours, and then place the beaker containing the mixed solution in an ultrasonic generator for ultrasonic impregnation. After vacuum drying, the sludge carbon loaded with active components is obtained.

[0062] Preferably, the precursor in step S3 is a nitrate, sulfate, acetate, chloride, etc. of the corresponding metal.

[0063] Preferably, the mass fraction of the active component supported on the catalyst in step S3 is 5-25 wt.%, wherein the molar ratio of manganese, cobalt and rare metal Ce is (1-5):1:(0.05-0.3).

[0064] Preferably, the frequency of the ultrasonic oscillation in step S3 is 10KHz to 80KHz, and the ultrasonic immersion time is 2 to 5 hours. Ultrasonic immersion can promote the uniform dispersion of active metals on the sludge carbon, more thoroughly penetrate into the internal structure of the sludge carbon, make the active components fully contact with the carrier, and ultimately improve the catalyst reaction activity.

[0065] Preferably, the silane coupling agent is one or more of N-aminoethyl-y-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, y-methacryloxypropyltrimethoxysilane, y-mercaptopropyltrimethoxysilane, and y-ureidopropyltriethoxysilane. The amount of the coupling agent added is 1-10% of the mass of the sludge carbon particles. Its function is to enhance the interfacial bonding force between the active component and the carrier, improve the dispersion of the active component on the surface of the carrier, prevent the active component from falling off or agglomerating during the reaction, and facilitate the adsorption of NO and NH3 during the denitration reaction, thereby improving the denitration activity of the catalyst.

[0066] S4. Microwave roasting: The sludge carbon loaded with active components in step S3 is placed in a microwave roasting furnace, roasted under an inert atmosphere, and ground into 60-80 mesh.

[0067] Preferably, the power of the microwave roasting furnace in step S4 is 1000-3000W, the microwave roasting temperature is 600°C-800°C, the microwave roasting time is 1h-3h, and the inert gas flow rate is 20ml / min-50ml / min. Compared with conventional muffle furnace roasting, microwave roasting can heat quickly and evenly, which helps to form a more uniform active phase and improve the activity and selectivity of the catalyst.

[0068] The working principle of the porous multi-element doped sludge carbon-based low-temperature denitrification catalyst prepared in this application is as follows:

[0069] (1) Sludge charcoal has a high specific surface area and can be used as an adsorbent to directly remove NO by physical adsorption. x Sludge charcoal also has a high carbon content and can be used as a solid reducing agent to directly reduce NO in a heterogeneous manner. The overall reaction is as described in R8 to R10. At high temperatures, its reaction rate is much higher than that of simple NH3 in a homogeneous reduction of NO. C+2NO→CO2+N2 R8C+NO→2CO+N2 R92CO+2NO→2CO2+N2R10

[0070] (2) The present application uses sewage sludge as a carrier and dopes it with multiple active components, giving full play to the synergistic effect between the multiple active components to improve the low-temperature catalytic activity, offset the negative impact of the hydroxylation reaction between H2O and the active sites, and reduce the sulfation of the active components. 3+ +Ce 4+ →Mn 4+ +Ce 3+ The redox cycle accelerates electron transfer and oxygen mobility, promoting the high-valence Mn with strong electron-withdrawing ability. 4+ The formation of Lewis acid increases the content of rare metal Ce 3+ The increase in Ce promotes the catalyst to produce abundant oxygen vacancies and surface active oxygen. Ce can also act as a sacrificial agent to combine with other active components and preferentially react with sulfate species, thereby protecting Mn and other active centers from sulfidation and deactivation. There is also a redox cycle between the two metal elements Mn and Co, namely, Co 3+ +Mn 3+ →Mn 4+ +Co 2+ , through the cycle to produce low-valent Mn 3+ , reducing the strong oxidizing ability of Mn species, forming stronger L-acid sites, reducing the over-oxidation of NH3 and the adsorption of SO2, making SO2 at a disadvantage in the competitive adsorption of NO. The addition of Co can also promote the oxidation of NO to NO2, promote the production of nitrates, and increase the number and types of acid sites on the catalyst surface.

[0071] (3) The rich pore structure of sludge carbon and the presence of various metal oxides play an important role in improving catalytic activity and resisting sulfur poisoning. After ternary molten salt-assisted sludge pyrolysis and one-step carbonization activation, it has an excellent mesoporous structure, which significantly reduces the thermal stability of ammonium sulfate and reduces its deposition on the catalyst surface, thereby improving the catalyst's sulfur resistance. The main substances of sludge carbon are SiO2 and Fe2O3 (such as Figure 2 As shown in the figure, the presence of SiO2 will inhibit the conversion of SO2 to SO3; Fe2O3 can regulate the distribution of electron clouds on the catalyst surface, synergize with the denitrification active components, and improve the sulfur resistance of the catalyst. In addition, sludge carbon also contains a variety of trace active metal oxides, such as ZnO, MnO, CeO2, NiO, CuO, V2O5 and ZrO2, which improve the reaction selectivity of direct heterogeneous reduction of NO by sludge carbon and reduce the activation energy of the reaction, and provide more possible pathways for the synergistic effect between the active components.

[0072] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a porous multi-element doped sludge carbon-based low-temperature denitration catalyst, characterized in that: The following steps are involved: Obtaining target sludge; Pre-treating the target sludge to obtain a sludge carbon precursor; The sludge carbon precursor is subjected to a one-step carbonization activation treatment assisted by a ternary molten salt to obtain porous sludge carbon particles; The porous sludge carbon particles are mixed with a manganese precursor, a cobalt precursor and a rare earth metal Ce precursor, dissolved in deionized water, and a coupling agent is added. After stirring and mixing evenly, ultrasonic impregnation treatment is performed, and after vacuum drying, sludge carbon loaded with active components is obtained; the coupling agent is a silane coupling agent or a phthalate coupling agent; The sludge carbon is subjected to microwave roasting treatment under an inert atmosphere to obtain a porous multi-element doped sludge carbon-based low-temperature denitration catalyst.

2. The method for preparing the porous multi-element doped sludge carbon-based low-temperature denitration catalyst according to claim 1, characterized in that: The target sludge is non-hazardous waste sludge; The step of pre-treating the target sludge to obtain a sludge carbon precursor comprises: The target sludge is placed in a forced air drying oven at 80-110° C. and dried for 24 hours to a constant weight, and then the dried sludge is crushed by mechanical crushing, and the crushed sludge is sieved with a 40-mesh sieve to obtain a sieved sludge carbon precursor.

3. The method for preparing the porous multi-element doped sludge carbon-based low-temperature denitration catalyst according to claim 2, characterized in that: The mechanical crushing is ball mill crushing, the rotation speed of the ball mill crushing is 200r / min to 400r / min, and the time is 3min to 10min.

4. The method for preparing the porous multi-element doped sludge carbon-based low-temperature denitration catalyst according to claim 1, characterized in that: The step of subjecting the sludge carbon precursor to a one-step carbonization activation treatment assisted by a ternary molten salt, and then successively filtering, washing and vacuum drying to obtain porous sludge carbon particles comprises: The sludge carbon precursor is mixed with ternary molten salt and heavy metal complexing agent, and then placed in a quartz boat; The quartz boat is placed in a tubular furnace from which the air has been exhausted, and the temperature is raised to 600°C to 900°C for carbonization activation treatment. After the carbonization activation treatment is completed, the temperature is lowered to room temperature, and the boat is washed with dilute hydrochloric acid and deionized water, and then vacuum dried to obtain porous sludge carbon particles.

5. The method for preparing the porous multi-element doped sludge carbon-based low-temperature denitration catalyst according to claim 4, characterized in that: The mixing ratio of the sludge carbon precursor, the ternary molten salt and the heavy metal complexing agent is 1:1-10:0.01-0.1; The ternary molten salt comprises lithium salt, potassium salt and sodium salt in a mass ratio of 1:1:1; The heavy metal complexing agent includes one or more combinations of citric acid, oxalic acid, ethylenediamine, diethylenetriamine, triethylenetetramine, sodium nitrilotriacetate, sodium ethylenediaminetetramethylenephosphate, ethylenediaminetetraacetic acid, tetrasodium diaminetetraacetic acid and diethylenetriaminepentacarboxylate.

6. The method for preparing the porous multi-element doped sludge carbon-based low-temperature denitration catalyst according to claim 4, characterized in that: The step of placing the quartz boat in a tube furnace from which air has been exhausted, heating it to 600° C. to 900° C. and then performing carbonization activation treatment; after the carbonization activation treatment is completed, cooling it to room temperature, washing it with dilute hydrochloric acid and deionized water, and vacuum drying it to obtain porous sludge carbon particles comprises: The quartz boat is placed in a tube furnace from which air has been exhausted, and the temperature is raised to 600°C to 900°C at a rate of 5°C / min to 20°C / min, and then carbonization activation treatment is performed; After being kept at a constant temperature for 2 hours, the activated sewage sludge was cooled to room temperature under an inert atmosphere, and then washed with dilute hydrochloric acid and deionized water for 5 to 10 times respectively to remove the molten salt crystallized on the surface and inside of the peat, thereby obtaining a porous structure. The sludge carbon with a porous structure is vacuum dried to obtain porous sludge carbon particles.

7. The method for preparing the porous multi-element doped sludge carbon-based low-temperature denitration catalyst according to claim 6, characterized in that: The inert atmosphere is nitrogen, helium or argon, and the flow rate of the inert atmosphere is 100-500 ml / min; The concentration of the dilute hydrochloric acid is 1 mol / L to 3 mol / L; The vacuum drying pressure is -0.06MPa to -0.08MPa, the vacuum drying temperature is 80°C to 110°C, and the vacuum drying time is 12h to 24h.

8. The method for preparing the porous multi-element doped sludge carbon-based low-temperature denitration catalyst according to claim 1, characterized in that: The porous sludge carbon particles are mixed with a manganese precursor, a cobalt precursor and a rare earth metal Ce precursor, dissolved in deionized water, a coupling agent is added, stirred and mixed evenly, ultrasonically impregnated, and vacuum dried to obtain sludge carbon loaded with active components, comprising: The precursor is a nitrate, sulfate, acetate or chloride of the corresponding metal; the silane coupling agent is one or more combinations of N-aminoethyl-y-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, y-methacryloxypropyltrimethoxysilane, y-mercaptopropyltrimethoxysilane and y-ureidopropyltriethoxysilane; the amount of the silane coupling agent added is 1% to 10% of the mass of the porous sludge carbon particles; The mass fraction of the active components loaded in the porous sludge carbon is 5wt.%-25wt.%; wherein the molar ratio of manganese, cobalt and rare metal Ce is 1-5:1:0.05-0.3; The ultrasonic frequency of the ultrasonic immersion treatment is 10KHz to 80KHz, and the ultrasonic immersion time is 2h to 5h.

9. The method for preparing the porous multi-element doped sludge carbon-based low-temperature denitration catalyst according to claim 1, characterized in that: The step of subjecting the active component-loaded sludge carbon to microwave roasting in an inert atmosphere to obtain a porous multi-element doped sludge carbon-based low-temperature denitration catalyst comprises: The power of the microwave roasting treatment is 1000W to 3000W, the microwave roasting temperature is 600°C to 800°C, and the microwave roasting time is 1h to 3h; The inert atmosphere flow rate is 20 ml / min to 50 ml / min.

10. A porous multi-element doped sludge carbon-based low-temperature denitrification catalyst, characterized in that: The product is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite support loaded type sulfated Mn-Co-Ce sulfur-tolerant catalyst for low-temperature flue gas denitration and preparation method of sulfur-tolerant catalyst

    CN105413715A

  • Medium temperature hydrophobic ozonolysis catalyst, application, and preparation method in the application

    CN109012690A

  • Green method for preparing multifunctional biochar from sludge and application of biochar

    CN115259131A

  • Catalyst for preparing single-walled carbon nanotube and preparation method thereof

    CN116159566A

  • Preparation method of activated carbon and low-temperature SCR (Selective Catalytic Reduction) denitration catalyst and flue gas denitration method

    CN116216717A

Cited By

  • Municipal sludge-based charcoal-rare earth concentrate composite SCR catalyst and preparation method thereof

    CN120054459A